Pengalaman Ibu Selama Masa Kehamilan Terkait Dukungan Keluarga Sebagai Upaya Pencegahan Stunting - Prihatanti, Nur Rohmah; Suryanti, Suryanti; Syarniah, Syarniah (Malang Journal of Midwifery (MAJORY), 2025)
Stunting is a condition where a child's growth is inhibited and they do not achieve their optimal physical and cognitive growth potential. Children who experience stunting can be detected from the age of 0-5 years. The mother's physical readiness during pregnancy through routine Antenatal care, taking iron tablets at least 90 tablets during pregnancy, carrying out Early Initiation of Breastfeeding after giving birth and providing exclusive breastfeeding for 6 months, the mother's psychological condition and family support can play a role in preventing stunting. The purpose of this study was to analyze the effect of family support for pregnant women as an effort to prevent stunting. The research was conducted in Banjarbaru City, South Kalimantan in 2024. This type of research is qualitative research with an in-depth interview method. The research sample was taken using the multistage random sampling method adjusted to the inclusion criteria and exclusion criteria. The research participants were 5 mothers who had children aged 0-2 years with an age range of 20-35 years and had met the research inclusion and exclusion criteria. The results of data processing were analyzed to assess the role of family support for mothers during pregnancy as an effort to prevent stunting. The results of the study showed that all participants (100%) knew about stunting in children and received family support during pregnancy. The form of family support varies for each mother, such as accompanying the mother during pregnancy check-ups and childbirth, providing care and nutrition during pregnancy and childbirth, preparing transportation plans to health facilities to avoid delays in handling childbirth. The existence of family support for mothers shows that mothers can go through their pregnancies comfortably, have their nutritional needs met and receive regular pregnancy check-ups so that their pregnancies are always healthy and free from stunting. Family support given to pregnant women during pregnancy has a significant influence in preventing stunting in children. Family support for pregnant women is expected to be continued until the child is born and care during growth and development as well as the importance of education from health workers in health services